A case study of the co-creation of the PrEP-SIC: a roadmap to support introduction of pre-exposure prophylaxis into new settings - Kathrine Meyers; Benjamin Lane; Jason Zucker; Yumeng Wu; Caroline Carnevale; Helen Burnside; Sarah Rowan; Eric Mayes; Gilianne Narcisse-Cempini; Melanie A. Gold; Lisa Saldana; Sarit A. Golub (BMC Health Services Research)
Abstract Background Pre-exposure prophylaxis (PrEP) is an effective biomedical intervention to prevent HIV, however uptake of PrEP across the United States has been slow and uneven. Understanding “what it takes” to implement PrEP so that it reaches those groups with the highest rates of new diagnoses is a critically important and understudied question. This descriptive case study details the development of an implementation science tool to guide the introduction of PrEP into new settings. Methods The Universal Stages of Implementation Completion (U-SIC) was customized for the provision of PrEP services (PrEP-SIC) by using subject matter expert recommendations to operationalize PrEP implementation processes into discreet activities. Six clinical sites used the PrEP-SIC retrospectively and prospectively to assess the extent to which the PrEP-SIC activities mapped onto their experience of introducing oral daily, event-driven, and injectable PrEP into their clinical settings. Interviews with site champions and PrEP-SIC data, including proportion of activities completed, were analyzed to refine the PrEP-SIC and identify patterns of implementation behavior. Results Five themes emerged about the accuracy of the PrEP-SIC to capture real world implementation processes: (1) Some PrEP-SIC activities, such as generating a costing plan, are not reflected in real-world implementation; (2) Sites do not define sustainment as achieving a set of quantitative program goals, but rather as being able to continue a program through staffing turnovers and shortages; (3) Written protocols and reviewing clinic data for program improvement were identified as two key factors that differentiate sites that reached sustainment from sites that did not; (4) The PrEP-SIC is assessed as somewhat useful to guide introduction of PrEP, but pairing the tool with technical assistance or coaching would optimize its utility; (5) Implementation is cyclical and recursive and pre-implementation activities may need to be revisited over time to ensure sustainment. Conclusions The case study has resulted in a PrEP-SIC that accurately captures an idealized implementation process. Using a well-defined set of implementation activities as a roadmap with supportive services to clinics, like technical assistance or implementation coaching, could direct implementation efforts and facilitate the integration of PrEP into new clinical settings that reach the people who need PrEP the most.